Comparação entre os resíduos finos recém-gerados e os depositados em aterros da indústria de rochas ornamentais - Silva, Tatiane Brito Perim da (2019)
The ornamental rock sector produces a significant amount of fine residues. Existing studies on the classification of these residues are still inconclusive. While some works consider them as Non-Inertes, others classify them as Inertes and even Dangerous. Another point that must be highlighted is the waste that has been deposited for several years and that also need to be studied in order to identify possible changes in its behavior with the environment. This study aimed to know the effect of aging of the fine residues generated by ornamental stone processing. Two moments were studied: the new residues (NRs) and the old residues (ORs). The samples were characterized according to size distribution, mineralogy, chemical composition and scanning electron microscopy (SEM). The classification of the residues followed the standards 10004, 10005 and 10006 of ABNT (2004). Regarding the characterization, no significant differences were observed between the studied cases; however, regarding the classification, it was observed that the behavior of the constituents of the residues changes over time, the concentrations of the analyzed parameters are higher in the NBs and tend to decrease in the RAs, from Non-Inertes (Class IIA) to Inertes (Class IIB).